PENGARUH PENDEKATAN PEMBELAJARAN MENDALAM TERHADAP DIMENSI PROFIL LULUSAN PADA MATA PELAJARAN IPAS KELAS V SISWA SD NEGERI 79 GURA - Afra Sastila Zalna Aman; Fitri Yanty Muchtar; Herdianty Ramlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the deep learning approach on the graduate profile dimensions in the Science and Social Studies (IPAS) subject for Grade V students at SD Negeri 79 Gura. The study employed a quantitative approach with a pre-experimental design of the one-group initial questionnaire and final questionnaire type, involving 17 students. Data were collected through questionnaires, observations, and tests, then analyzed using descriptive statistics and the Paired Sample t-Test. The results revealed a significant improvement in students' average scores, rising from 45.41 (initial questionnaire) to 66.76 (final questionnaire), with the lowest score increasing from 38 to 64 and the highest score from 48 to 70. The Paired Sample t-Test yielded a t-value of 25.523 with a significance level of 0.000 (p < 0.05), confirming the significant influence of the deep learning approach. Observations indicated positive development across graduate profile dimensions, particularly in faith and piety (89.22%), global citizenship (83.09%), critical reasoning (89.71%), and collaboration (92.16%). The deep learning approach proved effective in creating meaningful learning experiences, enhancing student engagement and conceptual understanding, and developing competencies aligned with the demands of the Merdeka Curriculum.